Y = mx + b. Use this equation for most linear functions. Enter the information that is given to you.
![- 6 = - 3(4) + b](https://tex.z-dn.net/?f=%20-%206%20%3D%20%20-%203%284%29%20%2B%20b)
Multiply the -3 and 4 to get 12.
![-6 = - 12 + b](https://tex.z-dn.net/?f=%20-6%20%3D%20%20-%2012%20%2B%20b)
Now divide the -12 from both sides.
![\frac{ - 6}{ - 12} = \frac{ - 12}{ - 12} + b](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%206%7D%7B%20-%2012%7D%20%20%3D%20%20%20%5Cfrac%7B%20-%2012%7D%7B%20-%2012%7D%20%20%2B%20b)
-12 cancels out on the right side and your left with
![- \frac {1}{2} = b](https://tex.z-dn.net/?f=%20%20-%20%5Cfrac%20%7B1%7D%7B2%7D%20%20%3D%20b)
Now re-enter the info back into the formula.
![y = - 3x - \frac{1}{2}](https://tex.z-dn.net/?f=y%20%3D%20%20-%203x%20%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20)
Then you've got your formula
First subtract the x variable on both sides so on the first equation youll have -6y=8x+60 then divide 6 on all variables which means youll have y=8/6x+10 and in the second equation you do the same thing and youll have y=-5/6x-11.5
Your answer would be 63.33. ((: ❤️
Answer:
![\sqrt{60}](https://tex.z-dn.net/?f=%5Csqrt%7B60%7D)
Step-by-step explanation:
The exponent of positive 1/2 is the square root of 60
60 ^1/2 = ![\sqrt{60}](https://tex.z-dn.net/?f=%5Csqrt%7B60%7D)
Add 10 to both sides
Step-by-step explanation:
x-10 = 8
x - 10 + 10 = 8+ 10
x = 18